Specific contact resistivity reduction in amorphous IGZO thin-film transistors through a TiN/IGTO heterogeneous interlayer - Jeong, Joo Hee; Seo, Seung Wan; Kim, Dongseon; Yoon, Seong Hun; Lee, Seung Hee; Kuh, Bong Jin; Kim, Taikyu; Jeong, Jae Kyeong (Nature Publishing Group, 2024)
Oxide semiconductors have gained significant attention in electronic device industry due to their high potential for emerging thin-film transistor (TFT) applications. However, electrical contact properties such as specific contact resistivity (rho(C)) and width-normalized contact resistance (RCW) are significantly inferior in oxide TFTs compared to conventional silicon metal oxide semiconductor field-effect transistors. In this study, a multi-stack interlayer (IL) consisting of titanium nitride (TiN) and indium-gallium-tin-oxide (IGTO) is inserted between source/drain electrodes and amorphous indium-gallium-zinc-oxide (IGZO). The TiN is introduced to increase conductivity of the underlying layer, while IGTO acts as an n(+)-layer. Our findings reveal IGTO thickness (t(IGTO))-dependent electrical contact properties of IGZO TFT, where rho(C) and RCW decrease as t(IGTO) increases to 8 nm. However, at t(IGTO) > 8 nm, they increase mainly due to IGTO crystallization-induced contact interface aggravation. Consequently, the IGZO TFTs with a TiN/IGTO (3/8 nm) IL reveal the lowest rho(C) and RCW of 9.0 x 10(-6) Omega<middle dot>cm(2) and 0.7 Omega<middle dot>cm, significantly lower than 8.0 x 10(-4) Omega<middle dot>cm(2) and 6.9 Omega<middle dot>cm in the TFTs without the IL, respectively. This improved electrical contact properties increases field-effect mobility from 39.9 to 45.0 cm(2)/Vs. This study demonstrates the effectiveness of this multi-stack IL approach in oxide TFTs.